Diagnostic and Prognostic ability of salivary MMP‐9 and S100A8 for periodontitis. (15th September 2020) - Kim, Hyun‐Duck; Kim, Sungtae; Jeon, Sumin; Kim, Seon‐Jip; Cho, Hyun‐Jae; Choi, Young‐Nim
Abstract: Objectives: Salivary diagnostic using matrix metalloproteinase (MMP) and S100 for periodontitis is a promising issue. However, its prognostic effect is still unclear. This study aimed to evaluate the prognostic ability of salivary MMP‐9 and S100A8 for periodontitis through non‐surgical periodontitis treatment clinical trial. Materials and Methods: Total 149 participants, 99 periodontitis and 50 healthy, were recruited. Among 99 non‐surgical periodontitis treatment participants, 74 participants were revisited after three months. Periodontitis was classified as stage II‐IV of new classification of periodontitis proposed at 2018. Enzyme‐linked immunosorbent assay kit was used to quantify salivary MMP‐9 and S100A8. Receiver operating characteristic curve was applied for diagnostic ability. Paired t test was applied for prognostic ability evaluating changes in salivary markers between pre‐ and post‐treatment. Results: Salivary MMP‐9 and S100A8 were associated with periodontitis ( p < .05). The screening ability of algorithm using salivary MMP‐9 and S100A8 for periodontitis was 0.86 ( p < .05). After treatment, reduction rate of salivary S100A8 and MMP‐9 was 83.7% and 23.5%, respectively, ( p < .05): only salivary S100A8 was superior compared to clinical parameters. Conclusion: Algorithm using salivary MMP‐9 and S100A8 showed high diagnostic power for periodontitis. Both salivary S100A8 and MMP‐9 showed prognostic ability for periodontitis, but S100A8 was better.